Managing to Adapt: Analysing adaptive management for planning, monitoring, evaluation, and learning - Desai, Harsh; Maneo, Gabriele; Pellfolk, Erica; Schlingheider, Annika (Oxfam, 2018)
Adaptive management is at the heart of ‘Doing Development Differently’. It emerges from stakeholders’ calls for development programmes to be more flexible and responsive to their contexts. Whether it becomes a mainstreamed practice depends on how much it is

OPM’s approach to assessing Value for Money - King, Julian; OPM (Oxford Policy Management, 2018)
This document offers practical guidance for assessing value for money (VfM) in international development programmes. Since 2016, evaluation expert Julian King has been working with OPM to develop and deploy a robust approach to VfM assessment. The approach combines cutting-edge evaluation practice with concepts from economic evaluation to respond to donor requirements for accountability and good resource allocation, as well as to support reflection, learning, and adaptive management.

DRG Center practical tips to implement more context-adaptive programming - Jacobstein, David (#AdaptDev, 2018)
Hi #adaptdevers, The cross-sectoral programs team in the DRG Center have been working in support of ways that programming can be made more aware of, and responsive to, context considerations that have to do with incentives and relationships between different actors - often called power dynamics or political economy. Following several discussions with field folks, we were asked to come up with simple and practical tips that could help staff to implement more context-adaptive programming, or to better Work Politically to use TWP jargon. With assistance from many of our field staff and partners, we've put together three documents (to start) that have now been cleared to share publicly: • Tips on Making Your Solicitations Invite Context-Driven Adaptive Programming - suggestions spanning most sections of a typical solicitation to better weave in Thinking and Working Politically. I'm particularly excited that this document contains embedded links to excerpts from a set of solicitations that model good practice. You can also find a summary of all the excerpts from real solicitations, and links onward to the public posting of those solicitations on Fed Biz Ops or Grants.gov, here. • Tips on Power Dynamics and Theories of Change - suggestions relevant to those working on project designs and logic models. • Tips for Better Use of Advisory Councils - suggestions to set up better advisory bodies that help you to incorporate political economy more automatically into your programmatic adjustments. I hope that you'll find these practical and helpful! Feedback is always welcome. Best, David

Dynamic gridlock: Adaptive Humanitarian Action in the Democratic Republic of Congo - Obrecht, Alice (ODI/ALNAP, 2018)